Nutrient resorption in two co existing Nothofagus species in southern Patagonia. - Bahamonde, Héctor Alejandro; Fernández, Victoria; Mattenet, Francisco Javier; Peri, Pablo Luis (University of Copenhagen, 2017)
Nutrient resorption understood as the “movement” of nutrients from leaves prior to abscission towards other tissues or internal stores has been suggested to be a key component of nutrient conservation in deciduous forest species (Ares and Gleason 2007). This strategy allows plants to use these nutrients for new growth or store, hence decreasing their dependence on soil nutrient availability. Native forests in southern Argentine Patagonia cover approximately 1.2 million ha, corresponding more than 95% of these forests to the southern beeches Nothofagus pumilio (lenga) and Nothofagus antarctica (ñire) (Peri et al. 2016). In general, both deciduous species occupy places with different environmental conditions. N. pumilio forest are mostly found as pure stands in well drained soils, while N. antarctica, a more plastic and rustic species, is displaced to more unfavourable site conditions including rocky or poorly drained soils, and more xeric zones in the limit with the Patagonian steppe. Nevertheless, there are small transitional areas where both species can coͲexist using the same sources of resources. The objective of this study was to compare nutrient resorption of both species growing together in two contrasting situations of environmental conditions and forest productivity. EEA Santa Cruz Fil: Bahamonde, Héctor Alejandro. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Fil: Bahamonde, Héctor Alejandro. Universidad Nacional de la Patagonia Austral; Argentina. Fil: Fernández, Victoria. Technological University of Madrid. School of Forest Engineering. Forest Genetics and Ecophysiology Research; España Fil: Mattenet, Francisco Javier. Consejo Agrario Provincial de Santa Cruz. Dirección Provincial de Bosques; Argentina. Fil: Peri, Pablo Luis. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Fil: ...